Implementation of SEMA Number 01 Years 2023: Summons Notice by Registered Mail in the Religious Court - Candra, Afrikal; Efendi, Faisal; Supardi, Elpi; Nurlaila, Nurlaila; Mulyawan, Fitra; Bulan Sari Siregar, Linda (Yayasan Lembaga Studi Makwa, 2025)
The purpose of this research is to examine how the implementation and impact of SEMA (Circular Letter of the Supreme Court) Number 1 years 2023. The research method used is a qualitative approach with in depth interview techniques and document analysis. Data were collected through literature study and observation of the implementation of SEMA number 1 years 2023. The analysis was conducted using a descriptive approach to illustrate the implementation of notifications through registered mail. The Religious Court involves two parties, namely the bailiff and the POS (PT. Pos Indonesia). The bailiff of the sends court summons notifications via postal service. The postal service delivers the court summons notifications through registered mail to the parties involved in the case while adhering to operational standards. However, there are still obstacles in its implementation, in improving the efficiency and effectiveness of the judicial process. Positive impact, especially in improving the judicial process Improvement in the quality of judicial services. The systematic arrangement of judicial procedures, accountability, and transparency, as well as the achievement of the principle of low-cost or affordable justice, also have negative impacts, particularly in the challenges of the latest system reforms, as well as the risks of prolonged trial delays and the risks of unlawful and unjust summonses. In reality, the POS often does not provide a summons to the litigant, which results in no information reaching the litigant.